Hubungan Kebiasaan Merokok dengan Kejadian Hipertensi pada Lansia di Wilayah Kerja Puskesmas Banyuputih Kabupaten Batang - Tegar Riniekso; Siwi Sri Widhowati; Isrofah Isrofah (Jurnal Gema Keperawatan, 2026)
Hypertension and smoking are two interrelated factors that have a significant impact on health, particularly among the older adult population aged 60 and older. Hypertension is often referred to as “the silent killer” because it frequently presents no obvious symptoms. Smoking is a modifiable risk factor that contributes to elevated blood pressure through the mechanism by which nicotine causes vasoconstriction of blood vessels. This study aimed to determine the association between smoking habits and the prevalence of hypertension among older adults in the service area of the Banyuputih Community Health Center, Batang Regency, Central Java Province. This study employed a quantitative approach with a cross-sectional design. The study population consisted of 333 older adults aged 60 years and older. A sample of 93 respondents was selected using consecutive sampling and calculated using the Slovin formula with a margin of error of 10%. Data were collected through blood pressure measurements using a digital sphygmomanometer, as well as a smoking habits questionnaire and a sociodemographic questionnaire. Data were statistically analyzed using the chi-square test with a significance level of ρ < 0.05. The prevalence of hypertension among older adults in this study was 73.1%, and the proportion of older adults who smoked was 64.5%. The majority of respondents were heavy smokers (38.7%). The chi-square test results showed a significant association between smoking habits and the incidence of hypertension among the older adults, with a p-value of 0.002. There is an association between smoking habits and hypertension among the older adults in the service area of the Banyuputih Community Health Center; therefore, a health program is needed to address smoking habits among the older adults.